Práticas de leitura e escrita docente em correspondência: atravessamentos de exercício de pensamento e cuidado de si - Lermen, Sabrina (Universidade do Vale do Rio dos Sinos, 2022)
This study aims to measure the problem of how reading and writing practices from teachers may operate with the thinking process which is intersected with their selfcare. Considering reading and writing as possibilities of subjective practices, which may be thought provoking and invite teachers to assume, through gaps, selfcare, because, interwoven in the exercise of occupying and taking care of themselves, they invite the other – their student – to also do it and accompanies him in this journey. Starting from the philosophy of difference, the theme of this research is to put into practice a way of experiencing reading and writing with teachers and realize how they can result into ways of subjectivity, care and thinking. Therefore, the key concepts of the research are thinking, selfcare, reading and writing, having as theoretical background authors such as Foucault, Sêneca, López, Larrosa, Kohan, Sibilia, Han, Skliar, Aquino, Olegario and Munhoz, among others. For such, a philosophical and literary workshop was developed with teachers from a public municipal chain of schools in Rio Grande do Sul, a state of Brazil. The workshop intended to operate other relations between reading and writing, to experiment other literary texts and to create time and space to read and write in order to generate the exercise of thinking and selfcare. Inspired in the capacity of the epistolary genre, based on Foucault and Sêneca, this dissertation was written in letters format, as were the workshop activities which suggested reading and writing letters. The productions of the workshop were examined through cartography, based on Kastrup, Passos and Escóssia, whose theorical-methodological clues indicate the company of the subjective process of the participants, the creation of common existential territory and peer approval. In this manner, three cartographical lines were created: time – discussion about different temporal crossings that marked the meetings, their importance in the reading and writing exercises and their suspension power; teaching – discussion about the ethic and aesthetic responsibility of teaching, the devaluation of the profession and the discussion of the power of pedagogical formation which allows time to read, write and think; meeting – discussion about the relations between teaching, reading, writing and subjectivity through experiences, the preparation for self-writing and the reverberations at school of a teacher who reads and writes. With that, it was possible to think of other ways of handling reading and writing at school regarding teacher training; modify the relations they establish to literature, to writing and reading, to themselves and to others; suspend time, create an experimentation space and to expand repertoire; and to live experiences of care through microphysical breaches that produced subjective effects and sparks of teaching enchantment.
Keywords: Cartas; Cuidado; Docência; Escrita; Leitura; Letters; Care; Teaching; Writing; Reading; ACCNPQ::Ciências Humanas::Educação